Bullying, violence and mental distress among young people. Cross-sectional population-based studies in Scania, Sweden. - Fridh, Maria (Socialmedicinsk tidskrift, 2018)
Maria Fridh disputerade med denna avhandling den 1 juni 2018 vid medicinska fakulteten, Lunds universitet. Lund University, Faculty of Medicine Doctoral Dissertation Series 2018:34, June 1st 2018. Maria Fridh, ST-läkare i socialmedicin. Socialmedicin och hälsopolitik, Institutionen för kliniska vetenskaper i Malmö, Lunds universitet. E-post: maria.fridh@med.lu.se